Analisis Resiko Usaha Pembesaran Lele Sangkuriang Probiotik Dan Non Probiotik (Study Kasus Usaha Lele Bapak Wahyu) Di Desa Karang Binangun II BMR OKU Timur - Munsiarum; Wiwiek Tri Setyarini (Jurnal Bakti Agribisnis, 2022)
The catfish farming business is a fairly developed business in the fisheries sector of East OKU district. Enlargement of catfish on limited land with high stocking density and poor feed management will worsen pond water conditions due to accumulation of organic matter that is toxic to catfish which causes stress and causes various diseases. Currently, probiotics are being used in fisheries for disease prevention efforts. The probiotic application itself gave birth to different attitudes and opinions for sangkuriang catfish rearing actors in Karang Binangun II Village, a stronghold that responded positively to revealing that real results had been obtained, in fact reducing production costs and boosting productivity. Meanwhile, from the camps that disagree, arguing is only wasteful and detrimental. The average cost incurred for probiotic sangkuriang catfish enlargement per 100 m² in one production cycle is Rp. 16,017,705 with an average total receipt of Rp. 21,098,500 so that the average income of probiotic sangkuriang catfish enlargement is Rp. 5,080,795. while the average cost incurred on non-probiotic sangkuriang catfish enlargement per 100 m² in one production cycle is Rp. 16,228,200 with an average total revenue received of Rp. 19,239,500 so that the average income for raising sangkuriang catfish non probiotics is Rp. 3,011,300. The cost risk of probiotic sangkuriang catfish rearing the coefficient of variance is 0.0063 while nonprobiotic sangkuriang catfish rearing the coefficient of variance is 0.0277, this is due to the large production costs that must be incurred by non-probiotic sangkuriang catfish rearing farmers, such as fertilization costs, liming costs , the cost of immunostimulants, and the cost of feed. For the production risk of probiotic sangkuriang catfish rearing with a coefficient of variance of 0.0048, while the non-probiotic sangkuriang catfish rearing with a variance coefficient of 0.0729 The results of the analysis show that the production risk of probiotic sangkuriang catfish rearing is smaller than that of nonprobiotic sangkuriang catfish rearing. this is due to the large production obtained on the enlargement of probiotic sangkuriang catfish. On the income risk of probiotic sangkuriang catfish rearing the coefficient of variance is 0.14 while on non-probiotic sangkuriang catfish rearing the coefficient of variance is 0.31. The results of the analysis show that the income risk of probiotic sangkuriang catfish enlargement is smaller than non-probiotic sangkuriang catfish enlargement, this is due to the low production cost of probiotic sangkuriang catfish with high production yields so that the income obtained on probiotic sangkuriang catfish enlargement is high.